2012
DOI: 10.4067/s0717-95022012000200055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Five Single Nucleotide Polymorphisms of ABCG5 and ABCG8 Genes on Ezetimibe Lipid-Lowering Response

Abstract: SUMMARY:In this study we evaluated the possible association between five single nucleotide polymorphisms in ABCG5 (rs6720173) and ABCG8 (rs11887534, rs4148211, rs4148217 and rs6544718) genes and ezetimibe response in Chilean hypercholesterolemic subjects. A total of 60 non-related hypercholesterolemic subjects, aged 18 to 65 years old were included in this study. These subjects were treated with ezetimibe (10mg/day) during one month. The ABCG5 and ABCG8 genotypes were assessed by PCR-RFLP. The genotype distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Therefore, we are fully aware that our results should be interpreted with caution and need to be replicated using a larger sample size of patients qualified in randomized manner to the groups treated with CYP3A4-metabolized statins (simvastatin or atorvastatin), non-CYP3A4-metabolized statins (fluvastatin, pravastatin or rosuvastatin) or ezetimibe. Ezetimibe, a selective cholesterol absorption inhibitor blocking Niemann-Pick C1 like-1 (NPC1L1) protein, is effective in sitosterolemia caused by ABCG5/ABCG8 mutations but Caamano et al reported no association between ABCG8 : rs11887534 polymorphism and lipid response (including HDL changes) to treatment with ezetimibe [ 36 ]. On the other hand, Zsiros et al revealed that NPC1L1 : c.-133A > G polymorphism modifies the ApoA1 response to ezetimibe and therefore, rather than altering HDL concentration, may alter the effects of ezetimibe on the structure and function of HDL particles [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we are fully aware that our results should be interpreted with caution and need to be replicated using a larger sample size of patients qualified in randomized manner to the groups treated with CYP3A4-metabolized statins (simvastatin or atorvastatin), non-CYP3A4-metabolized statins (fluvastatin, pravastatin or rosuvastatin) or ezetimibe. Ezetimibe, a selective cholesterol absorption inhibitor blocking Niemann-Pick C1 like-1 (NPC1L1) protein, is effective in sitosterolemia caused by ABCG5/ABCG8 mutations but Caamano et al reported no association between ABCG8 : rs11887534 polymorphism and lipid response (including HDL changes) to treatment with ezetimibe [ 36 ]. On the other hand, Zsiros et al revealed that NPC1L1 : c.-133A > G polymorphism modifies the ApoA1 response to ezetimibe and therefore, rather than altering HDL concentration, may alter the effects of ezetimibe on the structure and function of HDL particles [ 37 ].…”
Section: Discussionmentioning
confidence: 99%